Role of the nuclear envelope in the pathogenesis of age-related bone loss and osteoporosis - Vidal, Christopher (Nature Publishing Group, 2012)
The nuclear envelope is the most important border in the eukaryotic cell. The role of the nuclear envelope in cell differentiation and function is determined by a constant interaction between the elements of the nuclear envelope and the transcriptional regulators involved in signal transcription pathways. Among those components of the nuclear envelope, there is a growing evidence that changes in the expression of A-type lamins, which are essential components of the nuclear lamina, are associated with age-related changes in bone affecting the capacity of differentiation of mesenchymal stem cells into osteoblasts, favoring adipogenesis and affecting the function and survival of the osteocytes. Overall, as A-type lamins are considered as the 'guardians of the soma', these proteins are also essential for the integrity and quality of the bone and pivotal for the longevity of the musculoskeletal system.